Assessing dynamics of democratisation transformative politics, new institutions, and the case of Indonesia - Törnquist, Olle (Palgrave Macmillan, 2013)
"Grows out of attempts by academicians and activists to contribute to transformative politics by developing a way of acquiring better contextual sources and analysing the processes and problems of democratisation in a theoretically more inclusive way than in the mainstream assessments that have come to parallel the industry of measuring economic growth. The book summarises the critique of these approaches, suggests a comprehensive alternative framework, and shows how the alternative works in reality through a case study of the largest of the new democracies, Indonesia"-- c Provided by publisher